Consequences of Perioperative Serotonin Reuptake Inhibitor Treatment During Hepatic Surgery. Issue 5 (16th March 2021) - Starlinger, Patrick; Pereyra, David; Hackl, Hubert; Ortmayr, Gregor; Braunwarth, Eva; Santol, Jonas; Najarnia, Sina; Driedger, Michael R.; Gregory, Lindsey; Alva‐Ruiz, Roberto; Glasgow, Amy; Assinger, Alice; et al.
Abstract : Background and Aims: Platelet‐stored serotonin critically affects liver regeneration in mice and humans. Selective serotonin reuptake inhibitors (SSRIs) and serotonin noradrenalin reuptake inhibitors (SNRIs) reduce intraplatelet serotonin. As SSRIs/SNRIs are now one of the most commonly prescribed drugs in the United States and Europe and given serotonin's impact on liver regeneration, we evaluated whether perioperative use of SSRIs/SNRIs affects outcome after hepatic resection. Approach and Results: Consecutive patients undergoing hepatic resection (n = 754) were retrospectively included from prospectively maintained databases from two European institutions. Further, an independent cohort of 495 patients from the United States was assessed to validate our exploratory findings. Perioperative intake of SSRIs/SNRIs was recorded, and patients were followed up for postoperative liver dysfunction (LD), morbidity, and mortality. Perioperative intraplatelet serotonin levels were significantly decreased in patients receiving SSRI/SNRI treatment. Patients treated with SSRIs/SNRIs showed a higher incidence of morbidity, severe morbidity, LD, and LD requiring intervention. Associations were confirmed in the independent validation cohort. Combined cohorts documented a significant increase in deleterious postoperative outcome (morbidity odds ratio [OR], 1.56; 95% confidence interval [CI], 1.07‐2.31; severe morbidity OR, 1.86; 95% CI, 1.22‐2.79; LD OR, 1.96; 95% CI, 1.23‐3.06; LD requiring intervention OR, 2.22; 95% CI, 1.03‐4.36). Further, multivariable analysis confirmed the independent association of SSRIs/SNRIs with postoperative LD, which was closely associated with postoperative 90‐day mortality and 1‐year overall survival. Conclusions: We observed a significant association of perioperative SSRI/SNRI intake with adverse postoperative outcome after hepatic resection. This indicates that SSRIs/SNRIs should be avoided perioperatively in patients undergoing hepatic resections.